Dysbiosis in the oral microbiomes of anti-CCP positive individuals at risk of developing rheumatoid arthritis. Issue 2 (1st October 2020) - Cheng, Zijian; Do, Thuy; Mankia, Kulveer; Meade, Josephine; Hunt, Laura; Clerehugh, Val; Speirs, Alastair; Tugnait, Aradhna; Emery, Paul; Devine, Deirdre
Abstract : Objectives: An increased prevalence of periodontitis and perturbation of the oral microbiome has been identified in patients with rheumatoid arthritis (RA). The periodontal pathogen Porphyromonas gingivalis may cause local citrullination of proteins, potentially triggering anti-citrullinated protein antibody production. However, it is not known if oral dysbiosis precedes the onset of clinical arthritis. This study comprehensively characterised the oral microbiome in anti-cyclic citrullinated peptide (anti-CCP) positive at-risk individuals without clinical synovitis (CCP+at risk). Methods: Subgingival plaque was collected from periodontally healthy and diseased sites in 48 CCP+at risk, 26 early RA and 32 asymptomatic healthy control (HC) individuals. DNA libraries were sequenced on the Illumina HiSeq 3000 platform. Taxonomic profile and functional capability of the subgingival microbiome were compared between groups. Results: At periodontally healthy sites, CCP+at risk individuals had significantly lower microbial richness compared with HC and early RA groups (p=0.004 and 0.021). Microbial community alterations were found at phylum, genus and species levels. A large proportion of the community differed significantly in membership (523 species; 35.6%) and structure (575 species; 39.1%) comparing CCP+at risk and HC groups. Certain core species, including P. gingivalis, had higher relative abundance in the CCP+at risk group. Seventeen clusters of orthologous gene functional units were significantly over-represented in the CCP+at risk group compared with HC (adjusted p value <0.05). Conclusion: Anti-CCP positive at-risk individuals have dysbiotic subgingival microbiomes and increased abundance of P. gingivalis compared with controls. This supports the hypothesis that the oral microbiome and specifically P. gingivalis are important in RA initiation.